Posttraumatic Stress Symptoms and Pain Sensitization After Whiplash Injury: A Longitudinal Cohort Study With Quantitative Sensory Testing - Andersen, Tonny Elmose; Ravn, Sophie Lykkegaard; Carstensen, Tina; Ørnbøl, Eva; Frostholm, Lisbeth; Kasch, Helge (Frontiers in Pain Research, 2022)
Posttraumatic stress symptoms (PTSS) are common after whiplash injury and are associated with poor recovery. The acute stress response may lead to pain sensitization and widespread pain, thereby compromising recovery. To our knowledge, no longitudinal study has assessed the associations between early PTSS and pain sensitization over time using quantitative sensory testing (QST). The aim of this study was to compare participants with different levels of PTSS, as measured by the impact of event scale (IES; subclinical 0–8, mild 9–25, and clinical ≥ 26) at baseline (<10-day post-injury) and at a follow-up of 1, 3, 6, and 12-month post-injury on pain sensitivity, neck mobility, pain distribution, and pain intensity. In total, 740 participants were recruited from emergency units or general practitioners with acute neck pain after a whiplash injury. The clinical PTSS group showed increased pain sensitivity on all QSTs at all time points compared to the subclinical PTSS group. Also, the clinical PTSS group showed significantly lower neck mobility at all time points except for a 3-month follow-up compared to the subclinical PTSS group. Moreover, the clinical PTSS group showed more widespread pain and self-reported headache and neck pain intensity at all time points compared to the subclinical PTSS group. This study emphasizes that participants with clinical levels of PTSS constitute a high-risk group that is sensitized to pain early after the injury. Hence, screening for PTSS within the 1st week after whiplash injury for those who experience high levels of pain intensity and distress may be an important clinical procedure in the assessment and treatment of whiplash-associated disorders (WAD).